Prevalence of infection of broiler chickens with motile salmonellae - IORDANIDIS (Π. ΙΟΡΔΑΝΙΔΗΣ) P.; GEORGOPOULOU (Ι. ΓΕΩΡΓΟΠΟΥΛΟΥ) I.; GEORGIADIS (Γ. ΓΕΩΡΓΙΑΔΗΣ) G.; BOUGIOUKLIS (Π. ΜΠΟΥΠΟΥΚΛΗΣ) P. (Journal of the Hellenic Veterinary Medical Society, 2017)
The results of a five-year epidemiological survey for the evaluation of motile salmonella infection in broiler chickens are reported in the present study. Three to four-week-old birds from 184 flocks, raised in several areas of Northern Greece, were examined bacteriologically. Fifty-five out of the 184 flocks were asymptomatic and the birds were presented for preventive examination, whereas the rest 129 flocks suffered from various diseases. Bacteriological examination of caecal contents from at least ten birds of each flock was performed. Samples from the viscera were also examined bacteriologically. Clinical signs and lesions - when present – were correlated with the isolation of salmonella in the flock. According to the results of this survey, 5.9-20% of the flocks were infected. Higher incidence was noticed in other European countries. Furthermore, no considerable difference in the incidence of infection between asymptomatic and diseased flocks was observed. In conclusion, salmonellae were more easily isolated from the caecal contents than from the viscera.